2017
DOI: 10.1136/bmjstel-2016-000180
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing quality of medical care in low income and middle income countries through simulation-based initiatives: recommendations of the Simnovate Global Health Domain Group

Abstract: BackgroundQuality of medical care in low income and middle income countries (LMICs) is variable, resulting in significant medical errors and adverse patient outcomes. Integration of simulation-based training and assessment may be considered to enhance quality of patient care in LMICs. The aim of this study was to consider the role of simulation in LMICs, to directly impact health professions education, measurement and assessment.MethodsThe Simnovate Global Health Domain Group undertook three teleconferences an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 30 publications
(30 reference statements)
4
33
0
Order By: Relevance
“…Although the authors included qualitative data collection in addition to scoping review, it is likely that this did not capture all relevant LMICs SBME activities. However, it did reveal a distinct lack of surgically focused interventions 11 …”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although the authors included qualitative data collection in addition to scoping review, it is likely that this did not capture all relevant LMICs SBME activities. However, it did reveal a distinct lack of surgically focused interventions 11 …”
Section: Introductionmentioning
confidence: 98%
“…A scoping review and survey conducted by Puri et al revealed that its utilization is centred around either medical education, training and evaluation or the use of simulated participants. 11 Although the authors included qualitative data collection in addition to scoping review, it is likely that this did not capture all relevant LMICs SBME activities. However, it did reveal a distinct lack of surgically focused interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They send a clear message that good-looking simulation models are insufficient, and that robust evidence based on standardised measures are necessary for the field to advance, for it to get buy-in from health professionals and for it to be properly implemented in modern healthcare. Puri et al 3 make a similar case for advancing care in low-income and middle-income countries, and also that the scope of what might be called frugal simulations be widened to benefit many types of endeavour, a role that international agencies could champion (see figure 2). …”
mentioning
confidence: 99%
“…According to Andreatta (2017), the perks of using simulation may be even more substantial in these settings given greater disparities between the delivery of high-quality health care and patient access to that care. Although a recent literature review of health care simulation in LMIC concluded that simulation in these settings is feasible and promising, simulation in LMICs is not currently in widespread use and remains an area of opportunity for improving health care quality (Martinerie et al, 2018;Puri et al, 2017). One major barrier to the uptake of simulation in LMICs is the considerable personnel and financial resources needed for initiating and maintaining a program (Avila-Guerra, 2014).…”
mentioning
confidence: 99%